Security of industrial water supply and management - Atimtay, Aysel T. 1944; Sikdar, Subhas K. (NATO Science for Peace and Security Series C: Environmental Security, 2011)
Over time, the increased use of fresh water for agriculture and industry together with contamination from discharges of pollutants, mean that ever more areas of the planet are becoming water-stressed.  Because of the competing needs of communities and industry for fresh water, industry will be challenged to meet its growing demands for water, which is essential for producing the goods and services that would boost human welfare. Thus industry will need to learn how to cost-effectively purify and recycle its wastewater for reuse, ultimately approaching a net zero-discharge condition.  The chapters in this book, written by international experts, treat the technical issues of such treatment and water management, and also provide guidance on technologies, either existing or in development, that can potentially achieve the goal of recycle-reuse. The book will serve as a useful reference for academics, government and industry professionals alike